STUDENTS’ SPEAKING SKILL IN MICRO TEACHING PRACTICE IN UNIVERSITY OF PASIR PENGARAIAN - Rahayu, Pipit; Amelia, Wilda (JEE (Journal of English Education), 2018)
In the process of the learning activities, every student has different efforts in learning English and it would give different progress of their speaking skill. In this research, the purpose was to know students speaking skill through micro teaching practice. The data took from their video documentation. The research design is descriptive qualitative research while the sample was sixth semester students of English Study Program in 2016/2017 academic year. The result of the research was from their performance in micro teaching practice was in average category, the data showed that 78% were average level.